The Development of The Banking Industry And its Impact on Sustainable Development (Entrepreneurship Journal for Finance and Business, 2023)
The research aims towards measuring the impact of the development of the banking industry on sustainable development, especially after the development of the banking industry in recent years and the transition to digital banking services that have      achieved great profits for the banking industry     by applying it to the Iraqi banking industry during the period                                                                               (2004-2020), using the ARDL model, where the research deals with measuring the impact of the development of the banking industry represented by the independent variables (credit provided to the private sector to GDP,                                                                                                                                  Total deposits to GDP, and money supply to GDP) on sustainable development, which is achieved through key indicators, which are economic indicators, social indicators, environmental indicators, and institutional indicators, where these approved variables were expressed through indicators (per capita GDP, population ratio in regions urbanization, change in forest area, spending on research and development), and the research concluded the great developmental role of the banking industry to achieve sustainable development as well as the need to develop and provide credit for modern projects that support clean energy and green environment